2013
DOI: 10.1105/tpc.112.107854
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Repressor HANABA TARANU Controls Flower Development by Integrating the Actions of Multiple Hormones, Floral Organ Specification Genes, and GATA3 Family Genes inArabidopsis 

Abstract: Plant inflorescence meristems and floral meristems possess specific boundary domains that result in proper floral organ separation and specification. HANABA TARANU (HAN) encodes a boundary-expressed GATA3-type transcription factor that regulates shoot meristem organization and flower development in Arabidopsis thaliana, but the underlying mechanism remains unclear. Through time-course microarray analyses following transient overexpression of HAN, we found that HAN represses hundreds of genes, especially genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(133 citation statements)
references
References 66 publications
5
128
0
Order By: Relevance
“…We analyzed these B-GATAs also because both AtGATA23 and AtGATA19 (HANL2) had previously been implicated in specific biological processes. AtGATA23 is an early marker gene for lateral root initiation, and AtGATA18/HAN together with AtGATA19/ HANL2 has a described role in flower development (Zhao et al, 2004;De Rybel et al, 2010;Zhang et al, 2013). While our attempts failed to generate overexpression lines for the better studied HAN, we were successful in generating overexpression lines for AtGATA19/HANL2.…”
Section: Atgata23 and Atgata19 Are Distinct From Llm Domain-containinmentioning
confidence: 86%
See 2 more Smart Citations
“…We analyzed these B-GATAs also because both AtGATA23 and AtGATA19 (HANL2) had previously been implicated in specific biological processes. AtGATA23 is an early marker gene for lateral root initiation, and AtGATA18/HAN together with AtGATA19/ HANL2 has a described role in flower development (Zhao et al, 2004;De Rybel et al, 2010;Zhang et al, 2013). While our attempts failed to generate overexpression lines for the better studied HAN, we were successful in generating overexpression lines for AtGATA19/HANL2.…”
Section: Atgata23 and Atgata19 Are Distinct From Llm Domain-containinmentioning
confidence: 86%
“…HAN has an additional role in the establishment of cotyledon identity during embryogenesis, a defect that may result from the interference of HAN with the auxin transport machinery (Nawy et al, 2010;Kanei et al, 2012). Overexpression of HAN negatively interferes with the expression of a gene closely related to HAN, HAN-LIKE2 (HANL2; AtGATA19), as well as with the expression of GNC and GNL (Zhang et al, 2013). This suggested that the gain of HAN function might be compensated by the down-regulation of potentially functionally redundant B-GATAs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of HAN-BD and HAN-AD was used as positive control (Zhang et al, 2013). All constructs were confirmed by sequencing and then transformed into yeast strain AH109.…”
Section: Yeast Two-hybrid Assaymentioning
confidence: 99%
“…Female flower buds from greenhouse-grown cucumber line 3407 were fixed, embedded, sectioned, and hybridized with digoxigenin-labeled probes as described previously (Zhang et al, 2013). Digoxigenin-labeled sense and antisense RNA probes were PCR amplified with T7 and SP6 RNA polymerases (Roche) using gene-specific primers (Supplemental Table S1).…”
Section: In Situ Hybridizationmentioning
confidence: 99%